Blue Water and the Consequences of Alternative Food Security Policies in the Middle East and North Africa for Water Security - Larson, Donald F. (World Bank, Washington, DC, 2013)
In the Middle East and North Africa, food security and water security are tightly entwined. In particular, choices about the extent to which food security policies rely on trade rather than domestically produced staples have stark consequences for the region's limited water resources. This paper builds on previous modeling results comparing the cost and benefits of policies to protect consumers against surging international wheat prices, and expands the analysis to consider the consequences of the policies for water resources. A self-sufficiency policy is analyzed as well. Results suggest that trade-based food security policies have no significant effect on the sustainability of water resources, while the costs of policies based on self-sufficiency for water resources are high. The analysis also shows that while information about the water footprint of alternative production systems is helpful, a corresponding economic footprint that fully measures the resource cost of water is needed to concisely rank alternative policies in economic terms that are consistent with sustainable outcomes.